2019
DOI: 10.1021/jacs.8b10845
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Modification of N-Terminal Proline Residues Using Phenol Derivatives

Abstract: A convenient enzymatic strategyis reported for the modification of proline residues in the N-terminal positions of proteins. Using a tyrosinase enzyme isolated from Agaricus bisporus(abTYR), phenols and catechols are oxidized to highly reactive o-quinone intermediates that then couple to N-terminal proline residues in high yield. Key advantages of this bioconjugation method include (1) the use of air-stable precursors that can be prepared on large scale if needed, (2) mild reaction conditions, including low te… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
54
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(57 citation statements)
references
References 65 publications
2
54
0
Order By: Relevance
“…It readily oxidizes phenols that are appended with NHS-activated cargo molecules, allowing simple tyramine derivatives to be used as readily available and storable building blocks. Most importantly, in previous work, 14 we and others have found that it leaves native tyrosine residues on proteins untouched if they are within the secondary and tertiary structural elements of folded structure.The ability of tyrosinases to generate o-quinones on proteins is well documented, at least at high substrate concentrations. Tyrosinases and phenol oxidases have been known for decades to mediate crosslinking between proteins in meat 35 , whey 36 , and flour 37 via non-selective tyrosine-tyrosine, tyrosinecysteine, and tyrosine-lysine linkages.…”
mentioning
confidence: 84%
See 2 more Smart Citations
“…It readily oxidizes phenols that are appended with NHS-activated cargo molecules, allowing simple tyramine derivatives to be used as readily available and storable building blocks. Most importantly, in previous work, 14 we and others have found that it leaves native tyrosine residues on proteins untouched if they are within the secondary and tertiary structural elements of folded structure.The ability of tyrosinases to generate o-quinones on proteins is well documented, at least at high substrate concentrations. Tyrosinases and phenol oxidases have been known for decades to mediate crosslinking between proteins in meat 35 , whey 36 , and flour 37 via non-selective tyrosine-tyrosine, tyrosinecysteine, and tyrosine-lysine linkages.…”
mentioning
confidence: 84%
“…It readily oxidizes phenols that are appended with NHS-activated cargo molecules, allowing simple tyramine derivatives to be used as readily available and storable building blocks. Most importantly, in previous work, 14 we and others have found that it leaves native tyrosine residues on proteins untouched if they are within the secondary and tertiary structural elements of folded structure.…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…57,84,85 Chemical methodologies for protein labelling have vastly diversied and improved in recent years, showing ne-tuned reactivity and biocompatibility with labelling achieved within live cells. [86][87][88][89][90][91][92][93][94] One can anticipate that efficient articial enzymes can be made by adapting these novel technologies.…”
Section: Site-selective Chemical Modication Of Proteinsmentioning
confidence: 99%
“…Here, the ligation of an acyl‐donor peptide ester and N‐terminal α‐amine of the acceptor protein is catalyzed by mutated subtiligase. Recently, Francis and co‐workers reported a tyrosinase mediate labeling of N‐terminal proline with an oxidized phenol or catechol . The enzymatic methods provide excellent tools for the labeling of proteins.…”
Section: Single‐site Labeling Of Pre‐engineered Proteinsmentioning
confidence: 99%